PERAN PENGHULU DALAM MENENTUKAN PERWALIAN ATAS ANAK PEREMPUAN YANG LAHIR DI LUAR PERNIKAHAN - Harni Eka Wati; Patimah; Andi Intan Cahyani (Universitas Islam Negeri Alauddin Makassar)
Abstract The main problem of this research is what is the role of the penghulu in determining the guardianship of daughters born out of wedlock? The sub-problems are: 1. How to determine guardianship of a girl born as a result of pregnancy outside of marriage in the KUA, Kahu District, Bone Regency? 2. What are the considerations of the penghulu in determining guardianship of a girl born as a result of a pregnancy outside of marriage at the KUA, Kahu District, Bone Regency? This research is a field research using qualitative methods, in which the research focuses on the results of data collection from predetermined informants. The approach used in this thesis research is descriptive-qualitative because the data needed and used by researchers is in the form of information distributions that do not need to be quantified. The results of the research are the guardianship rights of girls who were born as a result of pregnancy outside of their parents' marriage, the head of the KUA Kahu District gave it to the guardian judge, because the child was only assigned to his mother and her mother's family. The implication of this research is that it is hoped that the head of the KUA or as the head of the Kahu sub-district, Bone Regency, maximizes efforts to determine marriage guardians for girls born as a result of pregnancies outside of marriage, and can minimize pregnant marriages outside of marriage. Keywords: Born out of wedlock, Penghulu, Guardianship of daughters.